2002
DOI: 10.1002/1521-3765(20020315)8:6<1467::aid-chem1467>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of the HIV-1 Envelope Glycoprotein gp160 Cleavage Site

Abstract: The selective proteolytic activation of the HIV‐1 envelope glycoprotein gp160 by furin and other precursor convertases (PCs) occurs at the carboxyl side of the sequence Arg508‐Glu‐Lys‐Arg511 (site 1), in spite of the presence of another consensus sequence: Lys500‐Ala‐Lys‐Arg503 (site 2). We report on the solution structural analysis of a 19‐residue synthetic peptide, p498, which spans the two gp160‐processing sites 1 and 2, and is properly digested by furin at site 1. A molecular model is obtained for p498, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The presence of a nearby carbohydrate moiety reduces cleavage efficiency, whereas a polybasic amino acid insertion within the loop or replacement of an uncharged amino acid with a basic residue serves to nullify the adverse influence of the carbohydrate, possibly by reversing the poor accessibility of the target sequence to protease (41,75). For HIV-1 gp160, a loop configuration for the furin cleavage motif was also proposed (60,63). If the dengue virus pr-M junction is located in a similar loop, the P5 deletion in TBEVpr/16681 may shorten or otherwise alter the local conformation of this loop in dengue virus prM in such a way that basic residues at more distal positions cannot compensate for the lack of P5 arginine for efficient cleavage.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of a nearby carbohydrate moiety reduces cleavage efficiency, whereas a polybasic amino acid insertion within the loop or replacement of an uncharged amino acid with a basic residue serves to nullify the adverse influence of the carbohydrate, possibly by reversing the poor accessibility of the target sequence to protease (41,75). For HIV-1 gp160, a loop configuration for the furin cleavage motif was also proposed (60,63). If the dengue virus pr-M junction is located in a similar loop, the P5 deletion in TBEVpr/16681 may shorten or otherwise alter the local conformation of this loop in dengue virus prM in such a way that basic residues at more distal positions cannot compensate for the lack of P5 arginine for efficient cleavage.…”
Section: Discussionmentioning
confidence: 97%
“…1c) has maximized the motif for recognition by a broad number of these furin-type PC enzymes. 38 While NMR techniques have elucidated the structure of a furin cleavage site in a 19-residue peptide from gp160, 53 atomic-resolution structural information for furin cleavage sites in proviral and protoxin proteins have been challenging to obtain, because the sites are typically found on flexible loop structures. To gain an understanding on the structural basis of toxin assembly and furin activation we crystallized a variant of anthrax toxin PA and solved its structure to 1.45-Å resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of processing at site2 may be rationalized on the basis of structural motifs. In fact, the 19mer NMR molecular model in TFE revealed that site2 is embedded in a helical segment, whereas site1 is in a exposed loop at the C-terminus of the peptide [12]. In contrast, the 41mer and 51mer, spanning extensive sequence of the gp160 cleavage region, were shown to represent very poor furin substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of site2 is unknown, though mutations of gp160 KAKR 503 sequence result in an unprocessed precursor [11]. Conformational differences between site1 and site2 may explain the preference of furin for site1 [12].…”
Section: Introductionmentioning
confidence: 99%